Unequal parenting of children with special needs in Singapore - Lu, Joy (2017)
Raising a child with special needs comes with atypical parenting responsibilities that are different from normative parenting. Atypical parenting becomes especially challenging when there is unequal access to social resources in society. This study seeks to explore inequality on two level –between and within families. Findings have revealed there is a difference in parenting across social class and this is attributed to different ratios of parental capital –economic/cultural/emotional. Despite being a nation that ranks top in Asia for gender equality, traditional gender roles still persists in present society. As such, women become the main caregiver and they faced increased maternal stress especially when caring for her special needs child.